Development of preanalytical criteria assessment of quality of vacuum blood collection systems affecting clinical examination of patients - S. P. Kazakov (SPb RAACI, 2020)
This paper presents comparative studies of preanalytical quality indices of vacuum gel systems (VGS) from four manufacturers, i.e., GL 795 (China), Vacuette (Austria), BD Vacutainer SST (USA) and Zdravmedtech (Russia). The analysis of the number of qualitative defects of the preanalytic phase of blood collection in vacuum gel tubes at the inpatient departments and in Department of Clinical Chemistry (preanalytic laboratory), in accordance with adopted criteria based on Russian industry standards, which are implemented with European indices of pre-analytic stage. The obtained results allowed us to identify a number of qualitative defects at pre-analytic stage for the vacuum gel systems from each manufacturer, including to summarize the data on number of these defects. Based on these results, the most common defects in each of the VGS presented by manufacturers are formulated. The results obtained can be used by manufacturers to improve the quality (structures) of the mentioned vacuum gel tubes.The results of the comparative characteristics of VGS of different manufacturers were evaluated by their influence on the indexes of hemolysis (IH), ictericity, lipemia. The resulting indices of ictericity and lipemia do not allow to use them as criteria for assessing quality of the gel systems. The frequency of IH occurrence in serum at > 50 conventional units in VGS of different manufacturers was studied. It was revealed, that IH in the range from 10 to 50 conventional units and more, can be used as a criterion of VGS quality.Comparison of routine biochemical parameters in VGS of different manufacturers, i.e., alanine aminotransferase, aspartate aminotransferase, direct bilirubin, lactate dehydrogenase (LDH), serum K+, was also carried out. It was found that the largest deviations from the average value were obtained for aspartate aminotransferase indices of more than 12.47% in Russian test tubes, and for direct bilirubin of more than 12.25% in Chinese test tubes and more than 9.15% in Russian test tubes. The study showed influence of IH upon quantitative values of lactate dehydrogenase for VGS from different manufacturers. It is proposed to use lactate dehydrogenase as an analyte. On this basis, it is possible to recommend a comparative quality assessment of vacuum gel systems, with IH cutoff level of more than 19 conventional units. It remains relevant to search for other analytes that can be used to assess the quality of VGS from different manufacturers. Some areas of research in biochemical testing are outlined. Preliminary data are obtained on usage of vacuum systems from different manufacturers for quality assessment, as well as conditions for performing these tests, along with the level of the hemolysis index of more than 10 conventional units.